Post-activation potentiation (PAP) in endurance sports: A review - Boullosa, D.; Del Rosso, S.; Behm, D. G.; Foster, C. (European Journal of Sport Science, 2018)
While there is strong support of the usefulness of post-activation potentiation (PAP) phenomenon in power demanding sports, the role that PAP could play in endurance sports has received less attention. The aim of this review is to present evidence for a better understanding of PAP in endurance athletes; and to discuss the physiological basis and methodological aspects necessary for better practices and designing further studies. A search for relevant articles on PAP and endurance trained athletes was carried out using Medline and ISI Web of Knowledge databases. Twenty-two studies were included in the review. The current evidence suggests the possible influence of PAP for performance enhancement after appropriate conditioning activities during warm up. Evaluation of PAP responses during testing, training and competition may be also important for athletes monitoring. There are many unresolved questions about the optimum load parameters for benefiting from PAP in both training and competition; and the role that PAP may exert for optimal performance while interacting with central and peripheral factors associated with muscle fatigue. Further studies should elucidate the association between PAP responses and long-term adaptations in endurance athletes.